Eriksonian Personality Research and Its Implications for Psychotherapy. Issue 6 (21st February 2013) - Marcia, James; Josselson, Ruthellen
Abstract: Erikson's comprehensive theory of human development has been empirically validated by personality researchers who have taken a status approach to the adult stages of the life cycle: Identity, Intimacy, Generativity, and Integrity. An understanding of these stages has implications for psychotherapy. Erikson's theory provides a descriptive language for where the individual stands currently within a psychosocial developmental context, where he/she might have gotten "stuck" in the past, and where she/he is heading in terms of developmental goals. This article attempts to link the empirical research on Erikson's developmental theory with an approach to therapeutic intervention that could be utilized by therapists from an array of therapeutic approaches. The authors, who are developmental, personality and clinical psychologists, illustrate the use of Eriksonian personality theory in psychotherapy by discussing case examples from their own psychotherapy practices.